Creating shared values as a new paradigm of Corporate Social Responsibility - Farid, Muhammad Mifta; Wati, Lily Rahma (Universitas Padjadjaran, 2024)
Background: Bank Sumsel Babel is faced with demands to focus on not only financial growth but also the positive impact on social and environmental fronts. The evolution of Corporate Social Responsibility (CSR) to Creating Shared Value (CSV) reflects a paradigm shift. As a regional development bank, Bank Sumsel Babel faces the demand to adopt CSV as an integral part of its CSR strategy to create a positive impact on society and the environment in the South Sumatra and Bangka Belitung regions. Purpose: This research explored the company’s strategy in implementing the Creating Shared Value (CSV) program as a new paradigm of CSR at Bank Sumsel Babel and analyzed the program publication to improve its reputation. Methods: This research used a descriptive qualitative research method to see the implementation of CSV at Bank Sumsel Babel. The researchers obtained data through interviews, observations, and document analysis. Results: Bank Sumsel Babel has successfully integrated the CSV approach into its CSR activities, particularly through the Bina Mitra program. This program has helped the bank address social issues such as education and community development and enhanced its business performance by building trust and loyalty among stakeholders. Conclusion: Companies can implement CSV-based CSR in some areas, while in other areas, they can use more traditional approaches, such as philanthropy or donations, to achieve a positive social impact. Implications: Bank Sumsel Babel can improve business performance and bring a positive impact on society through Creating Shared Value (CSV) programs as part of its CSR strategy.